EP-49 First reported case of preperitoneal herniation of small bowel causing intestinal obstruction after total extraperitoneal hernia [TEP] repair- case report and review of the literature. (9th August 2022) - Samarakoon, Lasitha Bhagya; Chandraprakash, Samip; Fernandes, Roland; Basnyat, Pradeep
Abstract: Introduction: A pre-peritoneal hernia is a very rare complication following laparoscopic inguinal hernia repair. We report a patient who developed a preperitoneal hernia following an accidental breach of peritoneum following Total extraperitoneal repair [TEP]. Even though it has been described following total abdominal pre peritoneal repair [TAPP], to the best of our knowledge this is the first reported case following TEP repair. Case presentation: A 57-year-old male underwent right inguinal hernia TEP repair on 20/10/2021. Initial recovery was uncomplicated but on POD 10 he developed sudden onset of vomiting and abdominal pain. Initial imaging showed small bowel obstruction without a definite transition point. We maintained a high index of suspicion for internal hernia and he was offered urgent diagnostic laparoscopy after careful counseling. A preperitoneal defect was noted with distended proximal ileum and collapsed distal ileum and colon. Small bowel run through which did not reveal any pathological abnormalities. A presumptive diagnosis of preperitoneal hernia was made, and the defect was closed with a running V lock suture. The patient made an uneventful recovery post-operatively. Conclusion: An inadvertent breach in peritoneum during TEP repair can lead to preperitoneal of small bowel and intestinal obstruction postoperatively. This is the first-ever reported case of this very rare complication following TEP that hernia and general surgeons should be aware of. A high degree of suspicion is needed and early diagnostic laparoscopy is indicated if suspected to avoid morbidity and mortality from bowel ischemia.